Simulation of sonar reverberation signal considering the ocean multipath and Doppler effect - Zhang, Sen; Wu, Jian; Yin, Tianqi (Frontiers in Marine Science, 2023)
To accurately model and simulate a sonar reverberation signal, the present study established four types of multipath sound ray seabed reverberation models that take the Doppler effect into consideration under the condition that the sound source and the hydrophone are separated. We then simulated the seabed reverberation signal considering a single-point separate transceiver and horizontal towed linear array in static or uniform linear motion. The seafloor reverberation signals in the element space and beam space were obtained, and the space-time characteristics and Doppler spread of our results were consistent with the theoretical analysis. The simulation results of the improved model show that under the transceiver device’s motion conditions, the amplitude of the reverberation signal envelope of the single-point transceiver and transceiver changes following the sine and cosine law. Accordingly, the signal pulse width and spectrum have changed, and the frequency shift of the horizontally dragged linear array reverberation signal is approximately sinusoidal with the linear array directivity angle. Our findings clearly show that the improved model presented in this study can simulate the reverberation signal significantly more accurately than the traditional models presented in the current literature.